Finite Difference Method for Stochastic Parabolic Equations - Şan, Mehmet Emin; Ashyralyev, Allaberen (Amer Inst Physics, 2 Huntington Quadrangle, Ste 1No1, Melville, Ny 11747-4501 USA, 2011)
In the present paper the single step difference schemes for the multi-point non local-boundary value problems for the stochastic parabolic equation are presented. The convergence estimates for the solution of these difference schemes are established. In applications this abstract result permit us to obtain the convergence estimates for the solution of difference schemes for the numerical solution of multi-point non-local boundary value problems for parabolic equations. The theoretical statements for the solution of this difference schemes are supported by the results of numerical experiments.
Keywords: Difference schemes; Stochastic parabolic equation; Convergence estimates